Impacts of land tenure and property rights on reforestation intervention in Ethiopia. (January 2018) - Legesse, Befikadu A.; Jefferson-Moore, Kenrett; Thomas, Terrence
Abstract: Land is a fundamental asset for social, political and economic sustainability, which provides ecosystem services, generate livelihood and accumulate wealth for the rural communities in developing countries like Ethiopia. Land degradation is one of the major environmental challenges in Ethiopia. In fact, public intervention in land management has conducted in the country in the last few decades to halt the problem but not successful due to socioeconomic, demographic, institutional, and other related factors. Among others, property rights to land may be one of the major factors that affect farmers' decision to invest in land management. Recognizing the significant role of land rights for land management is not new to the literature. However, there are few empirical in-depth case studies regarding its effect in reforestation intervention in developing countries like Ethiopia. This study, therefore, examines determinants of farmers' decisions to invest in reforestation interventions through focusing on land tenure and property rights. The study found out that land security is one of the most significant factors that affect farmers' decision to practice reforestation intervention.